Dampak Kontraksi Sektor Industri Terhadap Penyerapan Tenaga Kerja dan Pendapatan Rumah Tangga di Indonesia Sesudah Krisis (1999) Pendekatan Structural Path Analysis (SPA) - Endah Saptutyningsih (Universitas Islam Indonesia, 2005)
The objectives of this study are analyzing the impact of industry sector’s contraction to income of household institution and identifying how much it influences to employment. For measuring the impact of industry sector to household income, we use multiplier decom¬posision of SNSE. A Structural Path analysis is used to determine which households and which employment influenced by the contraction.The findings indicate that the greatest impact of industry sector’s contraction is on upper class household in urban. The industry sector which gives the greatest impact is a wood sector. That impact also influences a production and manual employee in urban.Keywords: household institution, employment, Multiplier Decompotition of SNSE, Structural Path Analysis.